An Examination of Women Experiencing Obstetric Complications Requiring Emergency Care: Perceptions and Sociocultural Consequences of Caesarean Sections in Bangladesh - Khan, Rasheda; Blum, Lauren S; Sultana, Marzia; Bilkis, Sayeda; Koblinsky, Marge (Journal of Health, Population and Nutrition, 2012)
Little is known about the physical and socioeconomic postpartum consequences of women who experience obstetric complications and require emergency obstetric care (EmOC), particularly in resource-poor countries such as Bangladesh where historically there has been a strong cultural preference for births at home. Recent increases in the use of skilled birth attendants show socioeconomic disparities in access to emergency obstetric services, highlighting the need to examine birthing preparation and perceptions of EmOC, including caesarean sections. Twenty women who delivered at a hospital and were identified by physicians as having severe obstetric complications during delivery or immediately thereafter were selected to participate in this qualitative study. Purposive sampling was used for selecting the women. The study was carried out in Matlab, Bangladesh, during March 2008August 2009. Data-collection methods included in-depth interviews with women and, whenever possible, their family members. The results showed that the women were poorly informed before delivery about pregnancy-related complications and medical indications for emergency care. Barriers to care-seeking at emergency obstetric facilities and acceptance of lifesaving care were related to apprehensions about the physical consequences and social stigma, resulting from hospital procedures and financial concerns. The respondents held many misconceptions about caesarean sections and distrust regarding the reason for recommending the procedure by the healthcare providers. Women who had caesarean sections incurred high costs that led to economic burdens on family members, and the blame was attributed to the woman. The postpartum health consequences reported by the women were generally left untreated. The data underscore the importance of educating women and their families about pregnancy-related complications and preparing families for the possibility of caesarean section. At the same time, the health systems need to be strengthened to ensure that all women in clinical need of lifesaving obstetric surgery access quality EmOC services rapidly and, once in a facility, can obtain a caesarean section promptly, if needed. While greater access to surgical interventions may be lifesaving, policy-makers need to institute mechanisms to discourage the over-medicalization of childbirth in a context where the use of caesarean section is rapidly rising. DOI: http://dx.doi.org/10.3329/jhpn.v30i2.11309 J HEALTH POPUL NUTR 2012 Jun;30(2):159-171